EVALUASI KEBIJAKAN PROGRAM FULL DAY SCHOOL PADA SEKOLAH UMUM - Risnita, Risnita; Asvio, Nova (Graduate Program Magister Manajemen Pendidikan, 2019)
The effectiveness of a policy can be determined after an evaluation of the policies conducted. Policy of Full day school endorsed by the Education Minister under the law on Permendikbud number 23 Year 2017 is considered still not been adopted universally in Indonesia, because there are still many things that need to be re-examined on the implementation, where there are still many weaknesses in the educational system full day school. For that Permendikbud is canceled by the issuance of Presidential Decree number 87 Year 2017 on Article 9, where the education system only full day school is optional, and not required to be applied in all schools Indonesian. Referring to the developed countries such as the US, Japan and Finland in the implementation of full day school is also not requiring all schools to implement these systems. In fact, Finland as the country ranks first in the world in the field of education version of MED NF, 2017, declared anti to full day school.